Design of Microstrip patch antenna for aircraft application - Muhammad Alif Naqiuddin, Mohd Nordin (2021)
In this project, a new noble design of single patch microstrip patch antenna with defected ground structure is presented for aircraft applications. The operational frequency for this new patch antenna is 5GHz. The size of the new patch antenna is only 27mm x 21.Smm, making it small and compact. The substrate that is used for the antenna construction is RT /Duroid 5880 and thickness of only 1.6mm, making it parallel with the concept of small and compact. The new patch is designed using High Frequency Structure Simulator (HFSS) software. Not only the software can be used to design, HFSS can also be used to simulate the newly design patch antenna where users can see their design's return loss, radiation pattern, gain and many more required variables.